2021
DOI: 10.3390/plants10122715
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compounds, Antitumor and Antimicrobial Activities of Dry Ethanol Extracts from Koelreuteria paniculata Laxm

Abstract: Koelreuteria paniculata Laxm. is used in traditional medicine and has various established biological activities, however, the species is considered to be a potentially invasive alien tree species for Bulgarian flora. However, there is still much to be studied about the phytochemical and biological characteristics of the species. The present study aimed to determine the chemical composition of the ethanol extracts of aerial plant parts, by GC-MS analysis, and to thereby evaluate their in vitro antitumor and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Various mechanisms of antimicrobial action of catechins are described by Górniak et al [ 42 ]. In this study, catechin was found only in the stem bark, which may be related to the most effective antibacterial activity reported in our previous study [ 27 ]. Epicatechin, which was also a well-represented flavonoid in the bark, is probably also relevant to the proven antimicrobial effect of this plant extract.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Various mechanisms of antimicrobial action of catechins are described by Górniak et al [ 42 ]. In this study, catechin was found only in the stem bark, which may be related to the most effective antibacterial activity reported in our previous study [ 27 ]. Epicatechin, which was also a well-represented flavonoid in the bark, is probably also relevant to the proven antimicrobial effect of this plant extract.…”
Section: Discussionsupporting
confidence: 52%
“…Its efficacy has been proven in vivo for various cancers (cervical cancer, leukemia, breast, prostate, liver, colon cancers, and glioblastoma). We also proved significant in vitro antiproliferative activity on the HT-29 cell line (human colon adenocarcinoma) for flower and leaf extracts [ 27 ]. The comparison between the amounts of flavonoids detected by HPLC-analysis and the antitumor activity found shows that the content of rutin is highest in these two plant parts (flowers and leaves) of all flavonoids, which gives us reason to assume its direct participation in the observed biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant activities of K. paniculata have been reported for different fractions of leaf extracts [4,17,18], carotenoid fraction of flowers [21], and extracts from aerial plant parts [20]. Antiproliferative activity of K. paniculata extracts and carotenoid fraction against HT-29 (colorectal adenocarcinoma), HepG2 (human hepatocarcinoma), MDA-MB-231 (human breast cancer cells), and PC3 (prostate carcinoma) tumor cell lines were also reported [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This group includes articles [1,2,7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], communications [27,28], and review papers [5,6,11,[29][30][31][32][33][34] with significant results applicable both in science and practice. The biology and ecology of plant secondary metabolites, their identification, and biological and therapeutic activity from different aspects of the phytochemistry of edible, aromatic, medicinal, or potentially medicinal plants are represented in a significant number of articles [3,8,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], as well as review papers [9,50,…”
mentioning
confidence: 99%